Teaching quality, social mobility and 'opportunity' in England: the case of the teaching and leadership innovation fund. Issue 3 (27th May 2021) - Steadman, Sarah; Ellis, Viv
ABSTRACT: Drawing on data from a study of the changing landscape for teachers' professional development (PD) in England, this paper addresses the provision of PD for teachers in schools serving high-poverty communities designated as 'Opportunity Areas'. Beginning with critical examination of relationships between teaching quality and social mobility, the paper reports on the analysis of organisations that won funding in the first round of the Teaching and Leadership Innovation Fund (TLIF), offered by the UK government in 2017. The paper shows how an economistic link between teaching 'quality' and the political imperative of 'social mobility' has restricted the provision of continuing PD for teachers in public schools, narrowing the scope of training to practices that have the capacity to further disadvantage children and young people experiencing economic and social inequity. As such, the CPD provision for teachers in these areas has the potential to reproduce rather than transform existing educational opportunities.